Evolving Evidence for the Optimization of Neoadjuvant Therapy in Triple-Negative Breast Cancer - Diogo Silva; Alexandra Mesquita (Breast Cancer: Basic and Clinical Research, 2022)
Representing 15% to 20% of all invasive breast cancers, adjuvant systemic treatment for early-stage, high-risk triple-negative breast cancer (TNBC) is preferentially done in the neoadjuvant setting based on a chemotherapy backbone of anthracyclines and taxanes. Pathological complete response to neoadjuvant treatment constitutes the main objective, regarding its correlation with oncological outcomes. The optimal neoadjuvant regimen to achieve the highest rates of pathological complete response is still under investigation, with the increasing knowledge on the molecular pathways, genomic sequencing, and immunological profile of TNBC allowing for the development of a wide array of new therapeutic options. This review aims to summarize the current evidence and ongoing clinical trials of new therapeutic options for the neoadjuvant treatment of TNBC patients.